PENGARUH KOMPETENSI, LINGKUNGAN KERJA NON FISIK, DAN SISTEM INFORMASI TERHADAP KINERJAPENGELOLA KEPEGAWAIAN DI LINGKUNGAN PEMERINTAH KABUPATEN BULELENG - Sang Made Jayadiputra; Komang Krisna Heryanda; Trianasari Trianasari (Universitas Bina Taruna Gorontalo, 2024)
The purpose of this study is to examine how information systems, non-physical work environments, and competency affect personnel managers' performance in the Buleleng Regency Government. In order to collect data for this study, a questionnaire is sent to respondents using a quantitative descriptive methodology. Personnel managers working for the Buleleng Regency Government make up the research's population, and the saturated sampling method is used in the sample process. As a result, the full 71-person population served as the sample. According to the research findings, competence significantly and favorably affects performance; (2) the non-physical work environment significantly and favorably influences personnel managers' performance; (3) the information system significantly and favorably influences personnel managers' performance; and (4) Information systems, competencies, and non-physical work environments all affect personnel managers' performance at the same time. The findings of the study support the hypothesis that, either separately or in combination, competence, information systems, and non-physical work environments improve the significant performance of human management.